"SPEEK-COF" Composite Cation Exchange Membrane for Zn-I2 Redox Flow Battery. Issue 10 (1st October 2022) - Chola, Noufal Merukan; Bavdane, Priyanka P.; Nagarale, Rajaram K.
Abstract : Zinc-based energy storage is increasingly getting attention owing to its outstanding characteristics over to the other systems. Their high abundance, user-friendliness, environmental benignity, and low reduction potential which can avoid unwanted hydrogen evolution are some of the attractive features. Appropriate membrane selection for the zinc-based redox flow battery is challenging. Herein we report the composite of SPEEK (sulfonated polyether ether ketones) with covalent organic frameworks (COF) as a potential membrane for zinc-based redox flow battery. Biphenyl-based knitting type COF was prepared, post sulfonated and blended with SPEEK. In a Zn/I2 redox flow battery system, the discharge capacity was found to be 19.8 AhL −1, 17.4 AhL −1, 15.1 AhL −1 for 20%, 15%, 10% SCOF loading respectively against 14.5 AhL −1 for pristine SPEEK at 20 mAcm −2 current density. The capacity was improved by about 36% higher than the neat SPEEK membrane. This improvement in the battery performance might be due to the higher ionic conductivity and hydrophilicity after SCOF loading. We found that the 15% loading was the maximum limit for the battery performance, beyond which the energy efficiency was found to be fading, which is due to the excessive dendrite growth on the membrane surface.